PERSONAL LIBRARY OF ANTANAS BARANAUSKAS - LIEPAITĖ, INGA; VERBICKAS, ANTANAS (Knygotyra, 2015)
A personal library of a well-known Lithuanian poet, linguist, mathematician, translator and Bishop of Sejny Antanas Baranauskas (1835–1902) has never been an object of any research in either the humanities or social studies before. Therefore, this study had to register all the known items from the Baranauskas personal library scattered around in various memory institutions of Lithuania and, first and foremost, in private collections. It has been found that the majority of items which belonged to Baranauskas were preserved in the Antanas Baranauskas and Antanas Vienuolis-Žukauskas Memorial Museum in Anykščiai (in total 29 items). Six items were found in the Wroblewski Library of the Lithuanian Academy of Sciences Rare Book Department. Last but not least, two volumes were found in Maironis Lithuanian Literature Museum and in the private collection of Stanislovas Abromavičius. Secondly, based on the findings of this research, the relation between the book and Baranauskas from his early years up to his appointment as Bishop of Sejny has been analysed. The study also describes Baranauskas’ methods to collect a personal library, its sources, size of the library, its topics and content. It highlights the peculiarities of the book culture of his personal library and the destiny of this collection. The study is focused on the less known biographic side of Baranauskas. For the famous poet, the book has been more or less the material to be used for self-development and perfection, to fight the often apparent grief and find creative inspiration; the book could be the remedy to serve the God, and finally, to carry out scientific research and educational activity. Most likely, the above mentioned points of view have to a great extent determined the topics for his personal library; a thoroughly collected and purchased library – like a piece of art in itself – during the period of the Russian Empire by using all the possible ways (buying the items, accepting them as a gift, making copies from the originals) and sources (from the new collections or reacquiring the old items) must have been a most handy tool to the poet, linguist, mathematician and lecturer in (at the time) the Kaunas Samogitian Priest Seminary. The collection of Baranauskas’ library was a targeted and conscious endeavour. Its origins can be traced back to the poet’s young days when he was a merely a youngster, embarking on a career of a scribe and stopped when he was an old age priest, titled as the Sejny Bishop. Handwritten dedications to Baranauskas, found inside the books, reveal important facts and dates of his personal life. The priest himself was most abstemious and restrained when it came to writing inscriptions inside the books as a present or marking the ownership inside his own books. The look of a book was not very important for the poet but he respected and appreciated it. Unfortunately, the destiny of Baranauskas’ personal library was unfavourable. After the poet’s death it was scattered around; a significant amount has probably gone to rack and ruin. That said, it should be noted that the storage rooms of Lithuanian major libraries still offer hope. There are hundreds of thousands of 19th c. printouts stacked in them, which have only recently been revised. Doubtless, a further search of items of one of the most famous 19th c. Lithuania’s poet Baranauskas personal library has to continue and that must be done only by collective efforts. Actualization of the poet and other Anykščiai county writers’ personal books and their promotion may help to assure and preserve the status of the literary county of Anykščiai.
Keywords: ...